Recurrence of Preeclampsia and the Risk of Future Hypertension and Cardiovascular Disease: A Systematic Review and Meta-Analysis. Issue 3 (September 2019) - Brouwers, L.; van der Meiden-van Roest, A.J.; Savelkoul, C.; Vogelvang, T.E.; Lely, A.T.; Franx, A.; van Rijn, B.B.
Abstract : ( BJOG . 2018;125:1642–1654) Preeclampsia, which is associated with cardiovascular disease (CVD), occurs in 3% to 5% of first pregnancies and has a recurrence rate of 15% in subsequent pregnancies. In fact, a pregnancy complicated by preeclampsia may suggest a disposition to CVD and help to identify women at risk for future disease. However, not all women with preeclampsia develop CVD. In the present review, the available evidence was evaluated on recurrent pregnancy complications, particularly preeclampsia, and future lifetime cardiovascular risk.